(untitled) (KYAMC Journal, 2017)
Objective: This study was done to determine frequency of extra-articular manifestations (ExRA) in patients with rheumatoid arthritis (RA) and its relation with treatment outcome in a tertiary care hospital, Dhaka. Methods: A cross sectional study was conducted upon 50 patients of rheumatoid arthritis of both gender aged ranging 30 to 60 years attending different medicine units of Shaheed Suhrawardy Medical College & Hospital during the period of May to October, 2011 who fulfilled the 1987 American College of Rheumatology criteria for RA. Demographic characteristics, extra-articular manifestations were recorded and some information was gathered by document review according to DAS28 (disease activity score 28.) Results: Among 50 patients female to male ratio was 9:1. The average age was 43.72±10.95 (SD) in years with maximum age 60 years and minimum age 30 years. Extra-articular manifestations were reported in 86.0% of patients. Hematological involvement (82%) was the most common extra-articular manifestation. Average DAS 28 was more in patients who had extra-articular manifestations than patients who had no extra -articular manifestation. Conclusion: Significant proportion of patients with female predominance visited at a tertiary care hospital due to RA. ExRA were present in a substantial proportion of a hospital based sample and is generally associated with a worse disease outcome. Hematological system involvement was the commonest. Early recognition and treatment are important to decrease disease activity. KYAMC Journal Vol. 6, No.-1, Jul 2015, Page 570-573